1986
DOI: 10.1093/carcin/7.12.1997
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of an oxidation product of p-phenylenediamine

Abstract: para-Phenylenediamine (p-PD), a widely used aromatic amine in the preparation of commercial oxidative-type hair dyes, has been previously demonstrated to have neither mutagenic activity to Salmonella typhimurium nor carcinogenic activity in rats and mice. In this study, the mutagenicity of p-PD after an oxidation by hydrogen peroxide towards S. typhimurium TA98 and its carcinogenicity in Wistar rats were examined both by topical application to the shaved skin and by s.c. injection. The oxidation product was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Components of temporary tattoos and hair dye ingredients, namely para-aminophenol (PAP) and para-phenylenediamine (PPD), have been reported to be carcinogenic and transformed in human skin [83,84]. However, other studies suggest that consumer or professional exposure to hair dyes poses no carcinogenic or other human health risks [85].…”
Section: Results – Melanoma Risk Factorsmentioning
confidence: 99%
“…Components of temporary tattoos and hair dye ingredients, namely para-aminophenol (PAP) and para-phenylenediamine (PPD), have been reported to be carcinogenic and transformed in human skin [83,84]. However, other studies suggest that consumer or professional exposure to hair dyes poses no carcinogenic or other human health risks [85].…”
Section: Results – Melanoma Risk Factorsmentioning
confidence: 99%
“…23 In fact, researchers have observed that the mammary gland of female rats was the primary target organ of the oxidation product of PPD. 24 This organ has also been shown to be highly susceptible to tumor induction by 2,4diaminotoluene and a wide range of N-substituted aromatic amines. The mechanism by which these compounds induce the tumors may be related to the presence of N,O-acetyltransferases in the mammary gland that are responsible for the formation of N-acyloxyarylamines.…”
Section: Commentmentioning
confidence: 99%
“…Topical and subcutaneous administration of p-phenylenediamine in mixtures like those used for hair dyeing induced tumours in the mammary gland, in the uterus and in soft tissues in rats (Table 7, [116]). …”
Section: Carcinogenicitymentioning
confidence: 99%